2016
DOI: 10.3389/fnhum.2016.00428
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiologic Correlates of Post-stroke Mood and Emotional Control

Abstract: Objective: Emotional disturbance is a common complication of stroke significantly affecting functional recovery and quality of life. Identifying relevant neurophysiologic markers associated with post-stroke emotional disturbance may lead to a better understanding of this disabling condition, guiding the diagnosis, development of new interventions and the assessments of treatment response.Methods: Thirty-five subjects with chronic stroke were enrolled in this study. The emotion sub-domain of Stroke Impact Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 67 publications
(74 reference statements)
1
8
0
Order By: Relevance
“…Abnormalities of the Alpha oscillation in the cerebral cortex, including the anterior cingulate cortex and the prefrontal cortex, might be modulated after rTMS over the prefrontal lobe by providing topdown control of thalamic and thalamocortical cortical Alpha oscillations and restoring functional links with the anterior thalamus. Additionally, the reduction in functional connectivity between the frontal and parietal lobes in patients with PSD resulted in an imbalance of the Alpha band power and the cerebral hemisphere, which might be associated with emotional control in post-stroke patients [22]. These ndings suggested that a decrease in negative emotional symptoms correlates with increased functional connectivity in the Alpha band, aligning with our observations.…”
Section: Analysis Of Phase Synchronization and Correlationsupporting
confidence: 89%
See 1 more Smart Citation
“…Abnormalities of the Alpha oscillation in the cerebral cortex, including the anterior cingulate cortex and the prefrontal cortex, might be modulated after rTMS over the prefrontal lobe by providing topdown control of thalamic and thalamocortical cortical Alpha oscillations and restoring functional links with the anterior thalamus. Additionally, the reduction in functional connectivity between the frontal and parietal lobes in patients with PSD resulted in an imbalance of the Alpha band power and the cerebral hemisphere, which might be associated with emotional control in post-stroke patients [22]. These ndings suggested that a decrease in negative emotional symptoms correlates with increased functional connectivity in the Alpha band, aligning with our observations.…”
Section: Analysis Of Phase Synchronization and Correlationsupporting
confidence: 89%
“…Doruk et al found that the Delta, Theta, Alpha, and Beta interhemispheric coherence decreased in patients with depression, possibly because pathological conditions that affected the integrity of neural tissue could cause changes in the structure and function of the damaged area. Doruk et al posited that observed the reduction in cerebral interhemispheric connectivity is indicative of post-stroke anatomical, adaptive and maladaptive changes in neural connections between damaged and undamaged cerebral hemispheres [22]. Studies have investigated the functional connectivity of amygdala subregions in patients with major depression, showing that the functional connectivity between the right central medial, lateral basal, and right middle frontal gyrus may be responsible for the neurobiological mechanism of anxiety-induced depression [23].…”
Section: Introductionmentioning
confidence: 99%
“…These changes have been thus identified through the use of biomarkers such as EEG and fNIRS, for instance, strong correlations between theta and delta band activities in the hippocampus and successful inhibitory mechanisms in rodent models (70). The use of EEG as a biomarker "tracker" thus becomes important because sensory inhibition reflects an automatic cortical inhibition function, which can be used as a measure of the brain's inhibitory status (71)(72)(73)(74). These findings support one of the study's main hypotheses that motor function deficits are associated with lower cerebral inhibitory activity when compared with a healthy control group.…”
Section: Discussionmentioning
confidence: 99%
“…With this concept, most recent studies of emotion assessment for stroke patients have utilized brain signals. Adamaszek et al studied the emotional impairment using the event-related potentials (ERP) of a stroke patient [ 15 ], Doruk et al studied the emotional impairment in stroke patients by comparing the emotional score in the Stroke Impact Scale (SIS) with the EEG features, the EEG power asymmetry and coherence [ 16 ]. Bong et al assessed the emotions of stroke patients by using EEG signals in the time-frequency domain [ 12 ].…”
Section: Related Workmentioning
confidence: 99%